Comparison of Resting-State Brain Activation Detected by BOLD, Blood Volume and Blood Flow - Zhang, Ke; Huang, Dengfeng; Shah, N. Jon (Frontiers in Human Neuroscience, 2018)
Resting-state brain activity has been widely investigated using blood oxygenation level dependent (BOLD) contrast. However, BOLD signal changes reflect a combination of the effects of cerebral blood flow (CBF), cerebral blood volume (CBV), and cerebral metabolic rate of oxygen (CMRO2). In this study, resting-state brain activation was detected and compared using the following techniques: BOLD using a gradient-echo echo planar imaging sequence (GE-EPI), CBV-weighted signal acquired using gradient and spin echo (GRASE) based vascular space occupancy (VASO), and CBF, using pseudo-continuous arterial spin labeling (pCASL). Reliable brain networks were detected from VASO and ASL, including sensorimotor, auditory, primary visual, higher visual, default mode, salience, and left / right executive control networks. Differences between the resting-state activation detected by ASL, VASO and BOLD might be potentially due to the different tSNR (temporal signal-to-noise ratio) and, the short post-labeling delay in ASL and in the spin-echo readout of VASO. It is also possible that the dynamics of spontaneous fluctuations in BOLD, CBV and CBF biologically differ by brain location.